PENGARUH KESELAMATAN KESEHATAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. MITRA AGUNG SWADAYA KELAYANG INHU - Minelly Primayanti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is motivated by the importance of human resource management in moving the company. The better the existing human resources are managed, the better the results obtained by the company. This research was conducted at PT. Mitra Agung Swadya Kelayang Inhu. The purpose of this study was to find out how much influence occupational health safety (K3) and employee discipline on work productivity of employees at PT. Mitra Agung Swadaya Kelayang Inhu. The sample of this study was taken as many as 51 respondents with the Slovin formula. In this study the method used is descriptive and quantitative. The data obtained from the results of the consultations were distributed directly to the field using the Random Sampling technique and then tested statistically through the SPSS program. in this study the results obtained are that Occupational Health Safety (K3) and Work Discipline have a positive and significant effect on Employee Work Productivity at PT. Mitra Agung Swadaya Kelayang Inhu. Keywords: Occupational Health and Safety (K3), Work Discipline, Employee Work Productivity.